1996
DOI: 10.1037/1040-3590.8.1.85
|View full text |Cite
|
Sign up to set email alerts
|

Confirmatory factor analysis of the Mattis Dementia Rating Scale in patients with Alzheimer's disease.

Abstract: Recent factor analyses of the Mattis Dementia Rating Scale (DRS; S. Mattis, 1973) have questioned the validity of its subscales, raising questions regarding their interpretation. This study examined the measurement structure of the standard DRS and of an abbreviated DRS form in a homogenous sample of 171 patients with Alzheimer's disease using (a) confirmatory factor analysis and (b) correlation of factors identified in the best fitting model with supplementary neuropsychological tests. We found confirmation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
13
0
1

Year Published

1998
1998
2008
2008

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 19 publications
0
13
0
1
Order By: Relevance
“…23,24 The added complexity of the hybrid model accounted for more variance in the data and left less unexplained variance in the residual. This hybrid model resolves the conflicting results present in the literature [2][3][4][5][6][7][8][9] and eliminates the necessity of allowing different factor structures for people with and without AD.…”
Section: Comparison Of Individuals With Vs Without Dementiamentioning
confidence: 76%
See 2 more Smart Citations
“…23,24 The added complexity of the hybrid model accounted for more variance in the data and left less unexplained variance in the residual. This hybrid model resolves the conflicting results present in the literature [2][3][4][5][6][7][8][9] and eliminates the necessity of allowing different factor structures for people with and without AD.…”
Section: Comparison Of Individuals With Vs Without Dementiamentioning
confidence: 76%
“…These results converge with the hypothesis that the AD process is multifactorial and may have differential effects varying by individual as well as the stage of the disease. [7][8][9] This heterogeneity suggests that within the observed overall cognitive decline in AD there may exist discrete decrement profiles that mask one another when measured together. In addition to increased variance in the specific cognitive domains in AD, there was also a changed pattern of covariance between cognitive domains.…”
Section: Comparison Of Individuals With Vs Without Dementiamentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the Mattis Dementia Rating Scale (DRS), which samples a comprehensive range of cognitive functioning, may be considered as an alternative to these two scales to detect and characterize cognitive impairment (Salmon et al, 1990;Shay et al, 1991). The DRS is one of the standardized mental status examinations that is widely used in the United States (Lucas et al, 1998;Salmon et al, 1990;Woodard et al, 1996). The test is found to have impressive reliability, with a test-retest reliability of .97 (Mattis, 1988), split-half reliability of .90 (Gardner et al, 1981) and internal consistency ranging from .75 to .95 (Vitaliano et al, 1984).…”
Section: Introductionmentioning
confidence: 99%
“…The MDRS is a widely used standardized mental status examination that provides a global measure of dementia derived from subscales for five cognitive capacities: attention, initiation and perseveration, construction, conceptualization, and memory. It is a reliable (Coblentz et al, 1973;Gardner et al, 1981;Smith et al, 1994;Vitaliano et al, 1984) and valid psychometric instrument for detecting and staging dementia (Gardner et al, 1981;Green et al, 1995;Monsch et al, 1995;Salmon et al, 1990;Shay et al, 1991;Smith et al, 1994;Troster et al, 1994;Woodard et al, 1996). Several studies have shown that the pattern of MDRS subscale scores can distinguish between AD and a variety of other dementing illnesses such as dementia with Lewy Bodies (DLB; Aarsland et al, 2003;Connor et al, 1998), Parkinson's disease (Paolo et al, 1995), Huntington's disease (Paulsen et al, 1995;Rosser & Hodges, 1994;Salmon et al, 1989), and progressive supranuclear palsy (Rosser & Hodges, 1994).…”
Section: Introductionmentioning
confidence: 99%